Strategi Misi sebagai Langkah Efektif dalam Penjangkaun Petobat Baru - Parhusip, Sarman; Joswanto, Andreas (Jurnal Ap-Kain, 2023)
This article entitled Mission Strategy as an Effective Step in Reaching New Converts.  Winning the souls for Christ was the purpose of the mission performed by missionaries to fulfill the Great Commission. In this paper, it was explained how the Mission Strategy carried out became more effective in reaching new converts.   By implementing the mission strategy, the obstacles in carrying out the mission could be overcome so the mission goal became effective.   A qualitative method with a literature approach was used in this article.  The finding of this article was that the execution of the mission was initiated by God if it was traced from the history in the Old Testament. God the Father instituted enmity between the descendants of the serpent and the descendants of the woman, the descendants of the woman would crush the serpents’ head, and the descendants of the serpent would crush his heels.  The statement of God is implemented through the existence of Jesus Christ by saving the whole world so that whoever believes in Him will not perish but has eternal life.AbstrakArtikel ini mengangkat judul Strategi Misi Sebagai Langkah Efektif Dalam Penjangkaun Petobat Baru. Memenangkan jiwa bagi kristus adalah merupakan tujuan dari misi yang dilakukan oleh para misionaris dalam memenuhi amanat Agung. Di dalam tulisan ini dipaparkan bagaimana Strategi Misi yang dijalankan  menjadi lebih Efektif dalam menjangkau petobat baru? Kemudian dengan menerapkan strategi misi, apa yang menjadi hambatan-hambatan dalam menjalankan misi dapat diatasi, sehingga sasaran bermisi menjadi efektif. Metode kualitiatif dengan pendekatan studi literatur artikel ini disusun. Temuan pemaparana artikel ini bermuara pada bahwa pelaksanaan misi digagas oleh Allah jika menelusuri kehistorisasnnya dalam Perjanjian Lama. Allah bapa mengadakan permusuhan antara keturunan si ular dan keturunan perempuan, keturunan perempuan itu akan meremukkan kepala si ular, dan keturunan si ular akan meremukkan tumitnya. Ungkapan Allah itu diimplementasikan melalui keberadaan Yesus Kristus dengan menyelamatkan seisi dunia agar siapa yang percaya kepada-Nya tidak binasa melainkan beroleh kehidupan yang kekal.